Self-Regulation as a Determinant of Cognitive Ability in Technology-Based Mathematics Learning Media - Hevitria, Hevitria; Arrosyad, Muhammad Iqbal; Tohir, Muhamad; Adilliyah, Adilliyah; Pratiwi, Saskia (Pelangi (e-Journal), 2024)
This research aims to analyze at teachers' self-regulation as a factor that determines their cognitive abilities in technology-based mathematics learning media. Self-regulation is a process where individuals consistently organize and manage their thoughts, emotions, behavior and environment to achieve academic goals. This study used a explanatory survey method with a quantitative approach. The instrument used in this research was a observation, interviews, documentation and questionnaire. The research subjects used were 10 STKIP MBB elementary school teachers consisting of grade 1 to 6 teachers and major teachers. The data analysis technique in this research uses simple linear regression. The results of the research reveal that Teacher Self-Regulation is a Determinant of Cognitive Ability in Technology-Based Mathematics Learning Media. The simple linear regression equation for the hypothesized self-regulation variable as a determinant of teacher cognitive abilities is: Ŷ = -27.664 + 0.938(85). The positive sign (+) indicates that the relationship between the independent variable and the dependent variable goes in one direction, which means that every increase or decrease in one variable will be followed by an increase or decrease in another variable, so that the higher the self-regulation, the higher the determinant teacher's cognitive abilities in learning media and vice versa